2015
DOI: 10.7227/rie.0025
|View full text |Cite
|
Sign up to set email alerts
|

Relationships among Taiwanese children's computer game use, academic achievement and parental governing approach

Abstract: This study examined the relationships among children's computer game use, academic achievement and parental governing approach to propose probable answers for the doubts of Taiwanese parents. 355 children (ages 11-14) were randomly sampled from 20 elementary schools in a typically urbanised county in Taiwan. Questionnaire survey (five questions) and statistical analyses were employed. The findings included the following: (a) parents' active engagement in computer game supervision had a significant impact on ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 35 publications
1
3
1
1
Order By: Relevance
“…Most parents thought that supervision is necessary to prevent distraction of child from work. Similar observations were also seen in previous studies [18,19]. It is of significant note that none of the parents under study were counseled by their pediatrician regarding the effects of usage of media devices on children and parents also did not actively seek advice.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Most parents thought that supervision is necessary to prevent distraction of child from work. Similar observations were also seen in previous studies [18,19]. It is of significant note that none of the parents under study were counseled by their pediatrician regarding the effects of usage of media devices on children and parents also did not actively seek advice.…”
Section: Discussionsupporting
confidence: 83%
“…The access to the computer is very less in this study as compared to studies from western countries [11,18,19]. This can be attributed to economic differences between developing and developed countries.…”
Section: Discussioncontrasting
confidence: 57%
“…For instance, a longitudinal study of 482 American adolescents with average age of 12 years reported that video game playing was associated with lower grade point averages (GPAs; Jackson, Von Eye, Witt, Zhao, & Fitzgerald, 2011 ). Recent studies have confirmed this finding from many parts of the world including Germany ( Rehbein et al., 2015 ), Taiwan ( Yeh & Cheng, 2016 ), Lebanon ( Hawi & Samaha, 2016 ), Norway ( Brunborg, Mentzoni, & Frøyland, 2014 ), Iran ( Haghbin, Shaterian, Hosseinzadeh, & Griffiths, 2013 ), and the United States of America (USA) ( Schmitt & Livingston, 2015 ; Wentworth & Middleton, 2014 ).…”
Section: Introductionmentioning
confidence: 71%
“…On the one hand, we can promote the development of college students’ mental health through their preferred INL. On the other hand, due to the adverse effects of Internet use, some people, especially parents, are afraid of too much exposure to the Internet ( Lei et al, 2012 ; Kuss et al, 2013 ; Lam, 2014 ; Yeh and Cheng, 2016 ; Cheung et al, 2018 ). They are worried that their children’s exposure to the Internet will affect their physical and mental health development.…”
Section: Discussionmentioning
confidence: 99%